Studies on the preparative isolation and stability of seven main anthocyanins from Yan 73 grape. (17th March 2014) - Tang, Ke; Li, Yang; Han, Yehui; Han, Fuliang; Li, Jiming; Nie, Yao; Xu, Yan
Abstract BACKROUND Seven anthocyanin monomers of Yan 73 grape were separated using preparative HPLC and identified by UPLC‐ESI‐MS/MS. The stabilities of the seven isolated anthocyanins to light, temperature and pH were also investigated. RESULTS Seven anthocyanin monomers were successfully isolated with an Xbridge Prep C18 column on a preparative scale. The pigments delphinidin‐3‐O‐glucoside, malvidin‐3‐O‐acetylglucoside and malvidin‐3‐O‐coumarylglucoside were yielded in a one‐step separation by preparative HPLC, with purities up to 99.9%, 91.7% and 95.5%, respectively. The pigments cyanidin‐3‐O‐glucoside, petunidin‐3‐O‐glucoside, peonidin‐3‐O‐glucoside, and malvidin‐3‐O‐glucoside were further purified with another elution method and their purities were all improved up to 99.9%. Monomeric anthocyanin degradation fitted a first‐order reaction model. The seven isolated anthocyanins were significantly more stable in the dark than under light. High temperature was also unfavourable for the stability of anthocyanins. The anthocyanins were more stable at lower pH than at higher pH. In addition, among these anthocyanins, delphinidin‐3‐O‐glucoside, malvidin‐3‐O‐acetylglucoside and malvidin‐3‐O‐coumarylglucoside were more susceptible to light, heat, and pH than the others. CONCLUSION A simple and clean isolation method of seven anthocyanin monomers from Yan 73 grape was established. The stabilities of the seven anthocyanin monomers to light, temperature and pH were different, but the trends in changes were similar. © 2014 Society of Chemical Industry